The Role of Tax Base Expansion and Taxpayer Compliance in Increasing Tax Revenue in Indonesia Through the Voluntary Disclosure Program (VDP) - Sitatun Nahriah; Firman Tatariyanto; Sugiyanto Sugiyanto (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research aims to analyze the influence of tax base expansion, taxpayer compliance, and the Voluntary Disclosure Program (VDP) on tax revenue in Indonesia, utilizing Gross Regional Domestic Product (GRDP) as a control variable. The theoretical framework is built upon the Slippery Slope Framework (SSF) popularized by Kirchler et al. (2008), which asserts that tax compliance results from two primary elements: the power of authority and trust in authority. Furthermore, this study employs Compliance Theory, rooted in the rational economic model (Allingham and Sandmo, 1972), which views taxpayers as rational individuals maximizing utility based on risks and sanctions. Using an explanatory quantitative method, the study conducts a panel data regression analysis on secondary data from 2018–2024 obtained from the Directorate General of Taxes and Statistics Indonesia. The results indicate that the number of taxpayers has a positive and significant effect on tax revenue, aligning with Pratama et al. (2024) regarding the positive correlation between registered taxpayers and state revenue. The implementation of VDP also demonstrates a significant positive impact, supporting Lestari et al. (2023) in that the program encourages the voluntary disclosure of unreported tax obligations. However, taxpayer compliance was found to have no statistically significant effect on tax revenue, confirming the argument by Muhammad & Sunarto (2018) that formal administrative compliance does not necessarily reflect the material compliance required to increase revenue. Conversely, the GRDP control variable proved to be a primary determinant, consistent with Wawire (2017) and Andrejovska & Pulikova (2018), who argue that fiscal capacity depends heavily on economic activity and the community's ability to pay. The study concludes that strengthening state revenue requires a balance between massive tax base expansion and building public trust through transparent policies.